The use of warm-up activities in speaking lessons in Yen Lang High School: a case study = Việc sử dụng các hoạt động tiền dạy nói trong giờ dạy nói ở THPT Yên Lãng. Điển cứu. - Hoàng, Thị Dự (ĐHNN, 2017)
Chapter 1: Literature Review. Chapter 2: Methodology. Chapter 3: Study results